Electronic retinal prosthesis for severe loss of vision in geographic atrophy in age-related macular degeneration: First-in-human use. Issue 3 (May 2021) - Stanga, Paulo E; Tsamis, Emmanouil; Siso-Fuertes, Irene; Dorn, Jessy D; Merlini, Francesco; Fisher, Andy; Crawford, Fiona IJ; Kasbia, Shakti S; Papayannis, Alessandro; Baseler, Heidi A; Morland, Antony B; Hanson, Rachel L.; et al.
Background: To date there are yet no available approved therapies for Geographic Atrophy (GA) secondary to age-related macular degeneration (AMD). Methods: Single site, non-randomized safety and efficacy study presenting the preliminary results in a cohort of five late stage AMD (GA) patients successfully implanted with the Argus II Retinal Prosthesis System (Second Sight Medical Products Inc., Sylmar, CA, USA). Extensive fundus imaging including retinal photographs from which the GA area was measured. A combination of custom and traditional tests designed for very low vision subjects assessed visual function in study subjects. A Functional Low-Vision Observer Rated Assessment was carried out to evaluate the impact of the system on the subject's daily life. In addition, a study to evaluate structural characteristics of the visual cortex of the brain was performed in one subject using magnetic resonance imaging. Results: Seven device-related adverse events were reported, four of which were classed as serious adverse events. Retinal detachment was reported in three patients and was successfully treated within 12 months of onset. Testing showed an improvement in visual function in three of five patients with the system turned on. Magnetic resonance imaging assessed in one patient after implantation indicates a selective increase in cortical myelin and thickness in visual brain regions 1 year post implantation. Conclusions: Epiretinal prostheses can successfully be implanted in those affected by GA secondary to late-stage AMD and can elicit visual percepts by electrical stimulation of residual neuroretinal elements and improve basic visual function in those affected.